Effect of hydrochloric acid on electrochemical behaviour of 430 stainless steel. (August 2014) - Jiang, M. F.; Li, X. L.; Yue, Y. Y.; Shi, P. Y.; Liu, C. J.
<x content-type="archive" xml:space="preserve">Abstract</x> The hydrochloric acid pickling process ensures high speeds with little pollution, for which a systematic study of the electrochemical behaviour of stainless steel in the oxidised hydrochloric electrolytes is of great significance. In this research, proper oxidiser was introduced into pickling solution with different concentrations of hydrochloric. Research indicated that as the concentration of hydrochloric acid rose, the charge transfer resistance Rt decreased, and that the decrease was more significant with high HCl content. When the HCl concentration was below 15%, the reaction was controlled by the anodic reaction, while the reaction was controlled by the cathodic reaction when the HCl concentration was above 15%. As the concentration of hydrochloric acid rose, the residue of oxide scales reduced and the surface of the stainless steel became soomther.